Normative Data for Handgrip Strength in Saudi Older Adults Visiting Primary Health Care Centers - Saad M. Bindawas; Vishal Vennu; Saada M. Al-Orf; Sulaiman A. Alshammari; Maysoon M. Al-Amoud; Philip C. Calder; May N. Al-Muammar; Adel A. Alhamdan (Medicina, 2019)
Background and objective: Handgrip strength (HGS) plays a vital role as a predictor of adverse health outcomes. Several studies have established HGS norms by age, sex, hand, occupation, culture or disability in different countries and for children in Saudi Arabia. However, standardized values for Saudi older adults have not yet been reported. Therefore, the current study was aimed to establish normative data for HGS in Saudi older adults visiting primary health care centers (PHCCs). Material and Method: In this descriptive cross-sectional study, HGS in kilograms was measured using a hydraulic hand dynamometer in Saudi older adults (n = 2045) aged ≥60 years visiting 15 PHCCs selected randomly from the five geographical regions of Riyadh, Saudi Arabia between January 2015 and April 2017. The average mean from three successive trials, standard deviations, and 95% confidence intervals presented for the left and right hands of men and women in six age groups (60−64, 65−69, 70−74, 75−79, 80−84, and 85+ years). The analyses were performed using the ANOVA test for all the age groups and to determine whether any differences exist between them. Results: The average mean HGS was significantly (p < 0.0001) differ by the left and right hands of men and women in six age groups. Conclusions: The current study presents specific norms for HGS in Saudi older adults by age, sex, and hand. Further studies are required to examine the utility of these norms for prediction of morbidity and mortality in this population.